Cognitive Function Estimation in Children with Tuberous Sclerosis - Troitskaya, L; Malahova, N (KnE Life Sciences, 2018)
Tuberous sclerosis (TSC) is a genetic disease characterized by cerebral structural abnormalities (such as cortical tubers, subependymal nodes and abnormal cerebral white matter) which are detected by means of neuroimaging methods (e.g., MRI). Typically, these events cause neurological complications (i.e., epilepsy). Objective: cognitive function estimation in TSC children considering severity and nature of clinical course of the disease. 15 children with tuberous sclerosis (i.e., experimental group) and 46 children with normal development (i.e., control group) aged 6-16 years old underwent neuropsychological examination. As a result, polymorphic disorders of higher mental functions were revealed in TSC children. Neuropsychological deficit (p<0.05) was detected. Namely, voluntary attention and memorization impairments were found in TSC children with normal development. Operational thinking disorders, immaturity of dynamic and kinesthetic movement basis, somatosensory gnosis, optical spatial or quasi-three-dimensional imaging, as well as insufficient oral/aural and semantical memorization were mentioned in TSC children with mental retardation. Regardless of mental development, TSC children demonstrate neurodynamic activity disorder (p<0.05) presented by slow task performance, increased exhaustibility and attention fluctuation. According to comparison between research findings and clinical course data, severity of cognitive disorders substantially depends on epilepsy onset age because early onset results in more severe developmental disorder (p<0.05). Since tuberous sclerosis is a dynamic disease with new potential symptoms arising over a lifetime, neuropsychological testing will provide timely mental status qualification and development of corrective actions to activate the cognitive activity of a child. Keywords: tuberous sclerosis, children, higher mental function (HMF) developmental disorders.